PENGARUH PENAMBAHAN KONSENTRAT MENGANDUNG ZnSO4 - ZnCu Isoleusinat TERHADAP BIOKIMIA DARAH KAMBING KACANG YANG MENGKONSUMSI SILASE SORGHUM- BUNGA TELANG (Effect of additional concentrate containing znso4 - zncu isoleucinate on boochemical blood of..... - Engelbertus D. P. Fernandez; Gusti A. Y. Lestari; I Gusti Ng. Jelantik (Universitas Nusa Cendana, 2021)
The research was to determine the effect of adding concentrate containing 150 mg ZnSO4 and 2% ZnCu Isoleucinate on the blood biochemistry of kacang goat consuming sorghum (Sorghum bicolor (l) Moench) - Bunga telang (Clitoria ternatea) silage rations. Using 12 kacang goats aged 13-14 months, with an average initial body weight of 14.40 Kg, KV: 14.93%. This study was designed using a randomized block design (RAK) consisting of 4 treatments and 3 replications. The four treatments studied were T1: Silage (adlibitum) without concentrate containing 150 mg ZnSO4 and 20% ZnCu Isoleucinate; T2: Silage (adlibitum) + 10% concentrate containing 150 mg ZnSO4 and 2% ZnCu Isoleucine; T3: Silage (adlibitum) + 20% concentrate containing 150 mg ZnSO4 and 2 % ZnCu Isoleucinate; T4: Silage (adlibitum) + 30% concentrate containing 150 mg ZnSO4 and 2% ZnCu Isoleucinate. The parameters observed consisted of: hemoglobin levels, erythrocytes, hematocrit, total plasma protein and leukocytes. Data was analysed used analysis of variance (ANOVA) and if it had a significant effect, continued with the BNT test to determine the difference between treatments (SPSS 21). The results of statistical tests showed that the treatment had a significant effect (P<0.05) on erythrocyte levels and hematocrit levels, but had no significant effect (P>0.05) on hemoglobin levels, total plasma protein levels and leukocyte levels. At the level of addition of 10% concentrate is the best for increasing erythrocytes and hematocrit of peanut goat.